Writings on the Apocalypse - Gregory I, Pope, approximately 540-604 (Fathers of the church ;, 2022)
"The Apocalypse or Book of Revelation is one of the most frequently discussed books of the biblical canon and arguably one of the most difficult to interpret. This volume contains three texts as examples of late ancient Christian interpretation of its intriguing visions. It also includes a comprehensive introduction to each text by its respective translator. 'Brief explanations of the Apocalypse' by Cassiodorus (c. 580), translated by Francis X. Gumerlock from Latin and published in English for the first time in this volume, served as an introduction to the Book of Revelation for Cassiodorus's students at the Vivarium, a monastery in southern Italy. Cassiodorus divided the Apocalypse into 33 sections, corresponding to the age of Jesus at his Passion, and expressed his belief that John's visions were revelations of the end of the world, including the Second Coming of Christ for judgment, the defeat of the Antichrist, the general resurrection, and the arrival of the heavenly Kingdom. 'Testimonies of Gregory the Great on the Apocalypse,' translated from Latin by Mark DelCogliano and also published here for the first time in English, is a collection of 55 excerpts on the Apocalypse from the writings of St. Gregory the Great (d. 604) compiled by an anonymous author. Drawn mainly from Gregory's 'Moralia,' but also from his 'Book on pastoral care' and homilies, the excerpts, which are arranged from Revelation 1.4 to 22.17, illustrate Gregory's grammatical exegesis of the Apocalypse, his interpretation of various figures in the Apocalypse, and his attempt to reconcile certain passages in the Apocalypse with seemingly contradictory texts from other parts of Scripture. The anonymous 'Greek scholia on the Apocalypse' contains 39 exegetical notes on chapters 1-14 of the Apocalypse, which reveal influences of Origen and Didymus the Blind, among others. The notes provide 'spiritual' interpretations of the various passages and give attention to the interpretation of certain words that appear in the Book of Revelation. This new translation from the Greek by T.C. Schmidt utilizes all the Greek editions. Furthermore, its introductory matter contains updates on the 'Scholia' from the latest scholarship and compares each 'scholion' with interpretations found in various patristic authors, mainly of Alexandrian heritage."--